Evaluasi Pembelajaran Pendidikan Agama Islam (Studi di SMK Muhammadiyah 1 dan SMK Muhammadiyah 2 Kota Palembang) - Nur Azizah; Muhammad Zainudin (Edification Journal : Pendidikan Agama Islam, 2020)
The research objective was to determine the evaluation of PAI Learning in SMK Muhammadiyah 1 and 2 Palembang city and technical evaluation conducted at SMK Muhammadiyah 1 and 2. This type of research is a qualitative descriptive study, data collection techniques using observation techniques, interviews, and documentation. Data analysis techniques use the framework of inductive and deductive thinking. The results of the study, the implementation of the evaluation is taken from the results of daily tests, midterm and final exam, the management of the evaluation includes planning, managing the implementation of the organization and evaluation. Technical Evaluation of PAI Learning leads to the cognitive domain, affective domain and psychomotor domain. PAI Learning Evaluation techniques implemented in SMK Muhammadiyah 1 and 2 are test and non-test techniques.